Cultural modification and adaptation of ESCAPE-pain programme for patients with knee OA in Malaysia - Che Hasan, Muhammad Kamil; Stanmore, Emma; Todd, Chris (2023)
Introduction: Enabling Self-management and Coping with Arthritic (knee) Pain using Exercise (ESCAPE-pain) is a programme of rehabilitation that integrates educational self-management and coping strategies for people with joint pain with an individualised exercise regimen for each participant. The implementation of ESCAPE-pain programme has been shown to be effective among populations in the United Kingdom, but in the Malaysian healthcare context, the population consists of various ethnic groups with three major ethnicities, Bumiputera, Chinese and Indian, which has created various cultures. Adaptation of the ESCAPE-pain programme from the English version to the Malaysian version is seen as necessary. Objective: Thus, this adaptation to the cultural context was the first step taken to consider the needs of different ethnicities within the Malaysian population in managing knee OA. Methods: The original ESCAPE-pain was translated into Malay language and presented among healthcare professionals managing knee OA and patients with knee OA in Malaysia. Common adaptations found through a systematic review of literature refer to current theories of cultural competence, consultation with experts, focus group discussions among the cultural agents, information about appropriate cultural risk factors, or a mixture of any of these. In this study, stages of adaptation by Barrera and Castro, (2006) were used to guide the process for adapting the ESCAPE-pain programme into the Malaysian context. Results: The Malay version of adapted ESCAPE-pain programme was tested through a feasibility study among 36 patients with knee OA in Malaysia. Conclusion: The adapted Malay version ESCAPE-pain programme may need further modification to facilitate the process of adoption in the local context. The programme in general appeared to reach the target participants and positively received by the patients with knee OA.